2015
DOI: 10.1038/ncomms8126
|View full text |Cite
|
Sign up to set email alerts
|

Widespread disruption of host transcription termination in HSV-1 infection

Abstract: Herpes simplex virus 1 (HSV-1) is an important human pathogen and a paradigm for virus-induced host shut-off. Here we show that global changes in transcription and RNA processing and their impact on translation can be analysed in a single experimental setting by applying 4sU-tagging of newly transcribed RNA and ribosome profiling to lytic HSV-1 infection. Unexpectedly, we find that HSV-1 triggers the disruption of transcription termination of cellular, but not viral, genes. This results in extensive transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
409
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(455 citation statements)
references
References 62 publications
40
409
4
2
Order By: Relevance
“…Similar to what we observed by Pol II ChIP-seq, the transcriptional changes were dominated by repression; the vast majority of mRNA genes exhibited decreased transcription, and little activation was observed. Interestingly, at later time points of infection, 4sU-seq reads mapped well beyond the 3= ends of thousands of genes, indicating a transcriptional termination defect that was most pronounced 7 to 8 h postinfection (40). At time points correlating with our work, only a subtle increase in the fraction of 4sU-seq reads mapping to intergenic regions was observed.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar to what we observed by Pol II ChIP-seq, the transcriptional changes were dominated by repression; the vast majority of mRNA genes exhibited decreased transcription, and little activation was observed. Interestingly, at later time points of infection, 4sU-seq reads mapped well beyond the 3= ends of thousands of genes, indicating a transcriptional termination defect that was most pronounced 7 to 8 h postinfection (40). At time points correlating with our work, only a subtle increase in the fraction of 4sU-seq reads mapping to intergenic regions was observed.…”
Section: Discussionsupporting
confidence: 64%
“…It is also possible that Pol II is recruited to promoters but does not stably associate in a manner that allows the polymerase to be cross-linked to the DNA or to be captured by ChIP. Recently, 4-thiouridine labeling and deep sequencing (4sU-seq) was used to evaluate ongoing transcription in 1-h windows during HSV-1 infection of human cells (40). Similar to what we observed by Pol II ChIP-seq, the transcriptional changes were dominated by repression; the vast majority of mRNA genes exhibited decreased transcription, and little activation was observed.…”
Section: Discussionsupporting
confidence: 49%
“…S7 and S8). Our findings, including identification of prematurely cleaved and polyadenylated transcripts by Northern hybridization in wild type, but not in ICP27 deletion mutant virus-infected cells, would not have been predicted by a recent report (14), which posited that ICP27 had no role in regulating cellular cotranscriptional pre-mRNA splicing or termination of cellular transcripts.…”
Section: Splicing Inhibition Mediated By Icp27 and Cytosine-rich Sequmentioning
confidence: 37%
“…Early studies indicated that, in an in vitro pre-mRNA splicing system, ICP27 may nonspecifically inhibit host pre-mRNA splicing, impairing spliceosome assembly as a result of interaction with SR protein kinase 1 (SRPK1) through ICP27's N-terminal RGG RNA-binding motif and/or interaction with spliceosome-association protein 145 (SAP145 or SF3B2) through ICP27's C-terminal domain (8,11). A recent communication reported that HSV-1 does not inhibit cotranscriptional splicing and proposed that previous reports of ICP27-induced splicing inhibition were artifacts, due to misinterpretation of run-on transcription (14). Indeed, splicing of only a few viral and cellular pre-mRNAs have been reported to be inhibited by ICP27 in infected cell culture.…”
mentioning
confidence: 99%
“…Ainsi, la capacité à recruter les ribosomes sur les ARN viraux est capitale pour le succès de l'infection [19]. [23]. Une étude de profilage ribosomique récemment réalisée chez un coronavirus murin a, au contraire, montré un mécanisme alternatif pour augmenter la production de protéines virales lors du cycle de réplication [24].…”
Section: L'étude De La Traduction Des Arnm Viraux Par Profilage Ribosunclassified